Deletion of Annexin A1 in Mice Upregulates the Expression of Its Receptor, Fpr2/3, and Reactivity to the AnxA1 Mimetic Peptide in Platelets - Zharkova, Olga (2023)
Annexin A1 (ANXA1) is an endogenous protein, which plays a central function in the modulation of inflammation. While the functions of ANXA1 and its exogenous peptidomimetics, N-Acetyl 2-26 ANXA1-derived peptide (ANXA1Ac2-26), in the modulation of immunological responses of neutrophils and monocytes have been investigated in detail, their effects on the modulation of platelet reactivity, haemostasis, thrombosis, and platelet-mediated inflammation remain largely unknown. Here, we demonstrate that the deletion of Anxa1 in mice upregulates the expression of its receptor, formyl peptide receptor 2/3 (Fpr2/3, orthologue of human FPR2/ALX). As a result, the addition of ANXA1Ac2-26 to platelets exerts an activatory role in platelets, as characterised by its ability to increase the levels of fibrinogen binding and the exposure of P-selectin on the surface. Moreover, ANXA1Ac2-26 increased the development of platelet-leukocyte aggregates in whole blood. The experiments carried out using a pharmacological inhibitor (WRW4) for FPR2/ALX, and platelets isolated from Fpr2/3-deficient mice ascertained that the actions of ANXA1Ac2-26 are largely mediated through Fpr2/3 in platelets. Together, this study demonstrates that in addition to its ability to modulate inflammatory responses via leukocytes, ANXA1 modulates platelet function, which may influence thrombosis, haemostasis, and platelet-mediated inflammation under various pathophysiological settings.